Corrosion and tribocorrosion behaviour of β-type Ti-Nb and Ti-Mo surfaces designed by diffusion treatments for biomedical applications. (1st August 2018) - Ureña, J.; Tsipas, S.; Pinto, A.M.; Toptan, F.; Gordo, E.; Jiménez-Morales, A.
Highlights: Effect of Nb and Mo diffusion treatments in Ti corrosion and tribocorrosion behaviour. β-Ti gradient surfaces with Young's modulus closer to that of bone exhibited better anticorrosive properties than cp-Ti. These Ti surfaces with Nb or Mo presented lower tendency to corrosion under tribological action. The Mo + NH4 Cl diffusion resulted in the hardest surface with the best tribocorrosion behaviour. Abstract: Corrosion and tribocorrosion behaviour of modified Ti surfaces through thermochemical treatments has been studied. Electrochemical Impedance Spectroscopy (EIS) and reciprocating sliding tests using a ball-on-plate tribometer under 1 N load and alumina as counter-material were used to evaluate the influence of Nb and Mo on titanium corrosion and tribocorrosion properties. Ti-Nb and Ti-Mo surfaces exhibited better anticorrosive properties than CP-titanium. Under tribological action the modified Ti surfaces showed similar coefficient of friction and lower tendency to corrosion compared to CP-Ti. Furthermore, Nb diffusion increased the repassivation rate with respect to Ti and Ti-Mo surfaces due to its stable passive film.